Preclinical In Vitro and In Vivo Evaluation of [18F]FE@SUPPY for Cancer PET Imaging: Limitations of a Xenograft Model for Colorectal Cancer. (13th February 2018) - Balber, T.; Singer, J.; Berroterán-Infante, N.; Dumanic, M.; Fetty, L.; Fazekas-Singer, J.; Vraka, C.; Nics, L.; Bergmann, M.; Pallitsch, K.; Spreitzer, H.; Wadsak, W.; et al.
Abstract : Molecular imaging probes such as PET-tracers have the potential to improve the accuracy of tumor characterization by directly visualizing the biochemical situation. Thus, molecular changes can be detected early before morphological manifestation. The A3 adenosine receptor (A3 AR) is described to be highly expressed in colon cancer cell lines and human colorectal cancer (CRC), suggesting this receptor as a tumor marker. The aim of this preclinical study was the evaluation ofF 18 FE@SUPPY as a PET-tracer for CRC using in vitro imaging and in vivo PET imaging. First, affinity and selectivity of FE@SUPPY and its metabolites were determined, proving the favorable binding profile of FE@SUPPY. The human adenocarcinoma cell line HT-29 was characterized regarding its hA3 AR expression and was subsequently chosen as tumor graft. Promising results regarding the potential ofF 18 FE@SUPPY as a PET-tracer for CRC imaging were obtained by autoradiography as ≥2.3-fold higher accumulation ofF 18 FE@SUPPY was found in CRC tissue compared to adjacent healthy colon tissue from the same patient. Nevertheless, first in vivo studies using HT-29 xenografts showed insufficient tumor uptake due to (1) poor conservation of target expression in xenografts and (2) unfavorable pharmacokinetics ofF 18 FE@SUPPY in mice. We therefore conclude that HT-29 xenografts are not adequate to visualize hA3 ARs usingF 18 FE@SUPPY.